Effects of Li2O on Structure and Viscosity of CaO-Al2O3-Based Mold Fluxes - Lifeng Chen; Kun Liu; Peng Han; Bin Yang; Lianghua Feng (Journal of Chemistry)
Since CaO-Al2O3-based mold fluxes are one of the most important mold flux systems in metallurgic processes, it is important to explore their structure characteristics and viscosity. Molecular dynamics simulation is performed to study the effect of w(CaO)/w(Al2O3) ratio on both the structural and viscosity properties of CaO-Al2O3-based mold fluxes. A systematic analysis of the structure and thermodynamics on CaO-Al2O3-based mold fluxes is carried out, and it is well known that the viscosity of mold fluxes is related to the structure. The results show that the formation of stable structures of Si-O in the mold fluxes was beneficial to reduce the probability of structural interconnection, degree of polymerization, and viscosity of the molten slag. In the cationic structure, the contents of Ca-O-Al and Ca-O-Si are more stable, the interconnection of the Ca-O-Al and Ca-O-Si network weakens, and the viscosity decreases. The tetrahedra [AlO4] and [SiO4] have similar structures, but they exhibit different thermodynamic and physical properties. Viscosity test shows that CaO/Al2O3 = 0.88–2 continuously increased, when the cosolvent content Li2O = 1%–4%, CaO-Al2O3-based mold flux viscosity decreased, the degree of network structure polymerization decreased, and the complex structure depolymerized. Increasing the water content in the cosolvent is beneficial to reduce the viscosity of the crystallizer.